Targeting Well-Balanced Solutions in Multi-Objective Bayesian Optimization Under a Restricted Budget - Gaudrie, D.; Riche, R. Le; Picheny, V.; Enaux, B.; Herbert, V. (Learning and Intelligent Optimization, 2019)
Multi-objective optimization aims at finding trade-off solutions to conflicting objectives. These constitute the Pareto optimal set. In the context of expensive-to-evaluate functions, it is impossible and often non-informative to look for the entire set. As an end-user would typically prefer solutions with equilibrated trade-offs between the objectives, we define a Pareto front center. We then modify the Bayesian multi-objective optimization algorithm which uses Gaussian Processes to maximize the expected hypervolume improvement, to restrict the search to the Pareto front center. The cumulated effects of the Gaussian Processes and the center targeting strategy lead to a particularly efficient convergence to a critical part of the Pareto set.